U-Shaped Relationship of Rare Earth Element Lanthanum and Oral Cancer Risk: A Propensity Score-Based Study in the Southeast of China - Fa Chen; Fa Chen; Qingrong Deng; Qingrong Deng; Yuxuan Wu; Yuxuan Wu; Yuying Wu; Yuying Wu; Jinfa Chen; Yujia Chen; Yujia Chen; Lisong Lin; et al. (Frontiers Media S.A., 2022)
As an important rare earth element (REE) extensively applied to industry, agriculture, and medicine, lanthanum (La) has attracted a host of health concerns. This study aimed to explore the relationship between La exposure and the risk of developing oral cancer through a case-control study with a large sample size. Serum La levels of 430 oral cancer patients and 1,118 healthy controls were detected by inductively coupled plasma mass spectrometry (ICP-MS). The association of La level with the risk of oral cancer was assessed in two ways: (1) as a continuous scale based on restricted cubic splines (RCS); (2) as a priori defined centile categories using multivariate logistic regression model, based on propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). The RCS revealed a non-linear U-shaped relationship between serum La and oral cancer risk. Serum La deficiency or excess was associated with an increased risk of oral cancer. When the La level was analyzed as a categorical variable, a similar U-shaped association was observed. Of note, compared to those with La concentrations of 0.243-0.341 μg/L (reference quantiles, 41st−60th), the risk was increased in those with the lower or higher quantiles (0.132-0.242 μg/L vs. 0.243-0.341 μg/L: OR = 1.80, 95%CI: 1.07-3.02; 0.342-0.497 μg/L vs. 0.243-0.341 μg/L: OR = 2.30, 95%CI: 1.38-3.84). The results were generally consistent with the PSM and IPTW analyses. This preliminary study provides strong evidence that there was a U-shaped relationship between serum La levels and oral cancer risk. Much additional work is warranted to confirm our findings.